Clinical outcome after switching therapy from ranibizumab and/or bevacizumab to aflibercept in central retinal vein occlusion - Pfau, Maximilian; Fassnacht-Riederle, Heidi; Becker, Matthias D.; Graf, Nicole; Michels, Stephan (Ophthalmic research, 2015)
Purpose: After 48 months, unresolved macular edema secondary to central retinal vein occlusion (CRVO) is present in more than half of the patients treated with ranibizumab/bevacizumab. Switching therapy to aflibercept, a more recent vascular endothelial growth factor-A (VEGF-A) inhibitor, as well as VEGF-B and placental growth factor inhibitor, might improve the clinical outcome in patients with CRVO who respond insufficiently to ranibizumab/bevacizumab. Methods: The presented study is a retrospective analysis of CRVO patients (n = 13) responding insufficiently to ranibizumab and/or bevacizumab (requiring treatment every 6 weeks or more frequently). Treatment in these patients was switched to aflibercept, which was administered based on a ‘treat and extend' regime. The injection interval, relapse-free interval, central retinal thickness, central retinal volume, visual acuity, and intraocular pressure (IOP) were evaluated prior to switching to aflibercept and at month 6 and year 1 after switching therapy. Results: From baseline to year 1 after switching therapy to aflibercept, the mean injection interval (primary end point) increased by 0.51 months (p = 0.023) and the relapse-free interval by 3.02 weeks (p = 0.003). The mean central retinal thickness decreased by 195.84 µm and the mean central retinal volume (6 mm diameter) by -1.81 mm 3 (p = 0.007). Correspondingly, the mean ETDRS score increased from 66.15 at baseline to 76.54 letters at year 1 after switching therapy to aflibercept (+10.38 letters, p = 0.021). The IOP was not statistically significantly affected (-1.2 mm Hg, p = 0.196). Conclusion: Switching therapy from intravitreal ranibizumab/bevacizumab to aflibercept in insufficiently responding macular edema secondary to CRVO elongates the injection interval and the relapse-free interval and provides an improved anatomical as well as functional outcome.
Gesehen am 03.07.2020